High Refractive Index Metamaterial Superstrate for Microstrip Patch Antenna Performance Improvement - Gao, Xi; Zhang, Yan; Li, Simin (Frontiers in Physics, 2020)
We propose a high refractive index metamaterial （HRIM）that is formed by symmetrically etching square metal patches on both sides of a dielectric plate. By reducing the gap of adjacent patches and the thickness of dielectric plate, the proposed metamaterial can suppress the diamagnetic response and enhance the capacitance coupling, so that the refractive index of the metamaterial is higher than 10 in wideband from 4 GHz to 8 GHz. Attributing to the property of high refractive index, the metamaterial can effectively improve the performance of a microstrip antenna when it is loaded as a superstrate. The measured results reveal that the impedance bandwidth of S11< -10 dB is 690 MHz (12.4%) and the maximum gain reaches to 13 dB at 5.6 GHz. The 1 dB and 3 dB gain bandwidth are 380 MHz (6.7%) and 590 MHz (10.3%), respectively. The antenna has a subwavelength profile of 0.19"λ" _"0" " (" "λ" _"0 " is the free space wavelength of the antenna central frequency). Furthermore, the profile can be further reduced to 0.15"λ" _"0" when the radiation patch of the antenna is surrounded by metasurface.